2u+38=-6(u+3)

Simple and best practice solution for 2u+38=-6(u+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2u+38=-6(u+3) equation:



2u+38=-6(u+3)
We move all terms to the left:
2u+38-(-6(u+3))=0
We calculate terms in parentheses: -(-6(u+3)), so:
-6(u+3)
We multiply parentheses
-6u-18
Back to the equation:
-(-6u-18)
We get rid of parentheses
2u+6u+18+38=0
We add all the numbers together, and all the variables
8u+56=0
We move all terms containing u to the left, all other terms to the right
8u=-56
u=-56/8
u=-7

See similar equations:

| 3x(x+0,3)=6,08(3x-0,1) | | 20b-16b+b-3b-b=5 | | 6y=9+45 | | 5(x+4)=4(7x-1) | | 0.5x2.6=1.3 | | -24=7(y-6)-4y | | 24=-8u+4(u+7) | | n^2+2n=59 | | 12.5=4x+2.5 | | 7x-8=4x19 | | 4y-45+y+36=8y-30 | | (x+20)+80=180 | | 3a/4+2=2a-8 | | 9(-2x-4)+12=-52 | | y=-20+4 | | 3x+2x+15=115 | | 2(4x-7=66 | | 3(2x-14)=-3(x-13) | | 5-b=4b-75 | | x+30+x=150 | | -6(4+6x)=-312 | | 9(p−79)=90 | | -16u—14u+-14u+11u=-10 | | 6x+5=3x+-10 | | 11y-9y-2y+3y-2y=9 | | -5x+30=-5 | | 2x+20+2x+10+x=180 | | -4(-6+1)+2x=5 | | 13y-12y=3 | | -14+y=-18 | | 6x/11=21 | | 7u-5u+2u+5u=18 |

Equations solver categories